Reactive extrusion of poly(L-Lactic Acid) with glycidol - Deenadayalan, E.; Lele, Ashish K.; Balasubramanian, M. (Journal of Applied Polymer Science, 2009)
Glycidol modified polylactic acid (PLLA) polymers have been prepared by reactive extrusion. Influences of residence time and the concentration of glycidol on the extent of reaction with different weight average molecular weight (45,000, 65,000, and 100,000) PLLA's were studied. Structure-property relationship has been established by measuring molecular, mesoscopic, and macroscopic properties. Under reactive extrusion conditions glycidol reacted with the end groups of PLLA to initiate chain extension. Low-molecular weight PLLA reacted with glycidol faster than the medium molecular weight PLLA, whereas high-molecular weight PLLA did not show significant reactions. The glass transition temperature, melting temperature, crystallization temperature, and heat of fusion were measured for unmodified and modified PLLA's. Chain extended PLLA had higher T(g) and T(m) than the unmodified samples. Time sweep rheological experiments were performed to test the melt stability of PLLA. Chain extended PLLA's were found to retain viscoelastic properties for much longer time than the unreacted samples. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 1391-1398, 2009
Keywords: biodegradable; reactive extrusion; Rheology; structure-property relations; Thermal properties